MOTIVASI KERJA APARATUR SIPIL NEGARA DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS TADULAKO PALU - Akbar, Akbar (Katalogis, 2017)
The purpose of this study was to determine the State Civil Administrative Work Motivation in the Faculty of Social and Political Sciences, University Tadulako. The theory used as a reference is the motivation theory of Frederick Herzberg, This study was descriptive with qualitative approach gained from in-depth interviews. The location of research at the Faculty of Social and Political Sciences. The informants as much as 7 (seven) employees with data sources include primary data and secondary data and data collection through interviews, observation, and documentation. Data analysis using descriptive data analysis model with a qualitative approach. The results showed that the motivation of employees, already well into the implementation of excellent service although there are some that have not been maximized, but the employees are motivated to work to serve the community in accordance with their respective duties because of a desire to provide services to the maximum in accordance expressed Herzberg is a motivator consists of achievement, recognition, work, responsibility and progress while the success factor is the relationship between superiors, engineering supervision, administrative policies, salary/wages and personal life. However, they still lack the motivation of some employees to earn achievements.